2019
DOI: 10.1038/s41598-019-49688-8
|View full text |Cite
|
Sign up to set email alerts
|

New crosstalk between probiotics Lactobacillus plantarum and Bacillus subtilis

Abstract: It was reported that oral administration of Bacillus favored the growth of Lactobacillus in the intestinal tract. Here, this phenomenon was confirmed by co-cultivation of Bacillus subtilis 168 and Lactobacillus plantarum SDMCC050204-pL157 in vitro. To explain the possible molecular mechanisms, B. subtilis 168 cells were incubated in simulated intestinal fluid at 37 °C for 24 h, and up to 90% of cells autolysed in the presence of bile salts. Addition of the autolysate to medium inoculated with Lb. plantarum SDM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…We recently demonstrated that four weeks of B. subtilis DE111 supplementation was associated with improved lipid parameters and endothelial function in healthy adults [ 21 ]. In addition, several in vitro and animal model studies have suggested that B. subtilis may modulate the mucosal immune system via production of antimicrobial peptides, exopolysaccharides, and quorum-sensing molecules, as well as through favorable modifications to the gut microbiota [ 22 , 23 , 24 ]. In elderly patients, intermittent use of B. subtilis strain CU1 increased fecal and salivary sIgA [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that four weeks of B. subtilis DE111 supplementation was associated with improved lipid parameters and endothelial function in healthy adults [ 21 ]. In addition, several in vitro and animal model studies have suggested that B. subtilis may modulate the mucosal immune system via production of antimicrobial peptides, exopolysaccharides, and quorum-sensing molecules, as well as through favorable modifications to the gut microbiota [ 22 , 23 , 24 ]. In elderly patients, intermittent use of B. subtilis strain CU1 increased fecal and salivary sIgA [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increased microbiota function of the spores induced by L-alanine was in accordance with the results in the anti-inflammatory and growth-promoting effect shown in Figures 5 , 6 . The improved intestinal microbiota by Bacillus administration might be caused by the metabolic activity and biological oxygen-capturing potential ( Yu et al, 2019 ), which are both closely related to the germination and proliferation of spores in the gut. Therefore, the results of the intestinal microbiota analyses also support the view that the germination of spores initiated by L-alanine could result in an increased probiotic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus spp. may also protect lactic acid bacteria in fermented foods from reactive oxygen species through their catalase activity ( 4 , 5 ). To clarify the physiological role of Bacillus spp.…”
Section: Announcementmentioning
confidence: 99%